Financial Performance, Dividend Policy, and Firm Value in Indonesian Consumer Goods Sector: 2019-2021 Study: Kinerja Keuangan, Kebijakan Dividen, dan Nilai Perusahaan pada Sektor Barang Konsumsi di Indonesia: Analisis 2019-2021 - Nurfitriana, Yunnisa; Widodo, Heri (Indonesian Journal of Public Policy Review, 2024)
This study investigates the nexus between return on assets (ROA), return on equity (ROE), dividend payout ratio (DPR), and firm value, represented by stock prices, within the consumer goods industry sector on the Indonesia Stock Exchange from 2019 to 2021. Utilizing a sample of 26 companies, employing Partial Least Square (PLS) analysis, the research reveals that neither ROA nor ROE significantly influences stock prices, and ROE exhibits no impact on DPR. Moreover, DPR fails to influence stock prices, and it cannot serve as an intervening variable between ROA or ROE and stock prices. These findings suggest a decoupling between financial performance metrics and market valuation within the consumer goods sector, urging a reconsideration of conventional wisdom regarding the determinants of stock prices in this industry Highlights : Limited Influence of ROA and ROE: The study reveals that return on assets (ROA) and return on equity (ROE) do not significantly impact stock prices in the consumer goods sector. Mediation Role of DPR: Dividend payout ratio (DPR) fails to mediate the relationship between ROA or ROE and stock prices, indicating its limited influence on market valuation within the sector. Implications for Market Valuation: The findings challenge traditional assumptions about the determinants of stock prices in the consumer goods industry, prompting a reevaluation of financial performance metrics' relevance in market valuation. Keywords: Consumer Goods Sector, Stock Prices, ROA, ROE, DPR